EXPERIENTIAL MARKETING SEBAGAI STRATEGI MENCIPTAKAN LOYALITAS GENERASI Z PADA OSING DELES CAFÉ AND RESTO BANYUWANGI - Moch Wafi Fakhrial; Permana Agung; Mohammad Riza Pahlevi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze marketing strategies through experiential marketing carried out by the management of Osing Deles Cafe and Resto Banyuwangi in order to create customer loyalty, especially generation Z. This research is a qualitative research with a case study approach. The research technique was carried out by observing and interviewing predetermined informants. The results of the study show that the marketing strategy carried out by the Osing Deles cafe manager through experiential marketing can be said to have succeeded in creating consumer loyalty, especially the millennial generation. As for the experiential marketing strategy, the first is related to sense experience, namely by designing unique and attractive café interiors, fragrant rooms, tempting food aromas and the availability of live music by bringing in famous singers. The second relates to the feel experience, namely by providing friendly service to customers and providing promotions such as price discounts and purchases 2 get 1 free. The third relates to the think experience, namely by providing a variety of unique food and beverage menus so that consumers have many menu choices to choose from. ordered. The fourth is related to act experience, namely by designing rooms with traditional themes to introduce and preserve the culture of the archipelago, especially the Osing tribe so that young people also know about the rich culture that exists. The fifth relates to relate experience, namely by providing solutions to complaints that customers feel related to services and menus ordered and serving them well.